2015
DOI: 10.1111/jonm.12278
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of advanced nurse practice: its existence and regulatory dimensions from an international perspective

Abstract: Nurse managers need to know that criteria for the regulation of advanced practice are in place and reflect the minimum requirements for safe practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…[40][41][42][43] Those competency mapping developments for APN closely related to Anglo-Saxon countries show that despite differences in APN role development approaches due to different healthcare system needs response, they share commons traits when working in identifying core APN competencies no matter the specific role described/ 4.2 Encourages individuals to share any issue or problem that may affect their personal development and any idea or suggestion related to this, helping them solve their problems in an objective or constructive way.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43] Those competency mapping developments for APN closely related to Anglo-Saxon countries show that despite differences in APN role development approaches due to different healthcare system needs response, they share commons traits when working in identifying core APN competencies no matter the specific role described/ 4.2 Encourages individuals to share any issue or problem that may affect their personal development and any idea or suggestion related to this, helping them solve their problems in an objective or constructive way.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of the similarities and differences of international regulation of ANPs found that national regulation occurs in Ireland, Japan, New Zealand, Singapore, Hong Kong, Australia, and the USA, but not in the UK (Carney, 2016). This raises the question of why the UK has not followed suit.…”
Section: What About Compulsory National Regulation?mentioning
confidence: 99%
“…Expansion of the current nursing role, or formally recognizing the ANP role, is consistent with recommendations from the World Health Organization and the Organization for Economic Co‐operation and Development to increase utilization of advanced clinical nurses in health care. The benefit to Danish nurses on the global stage is to modernize the role of nursing in Denmark, consistent with that seen in other countries . It is a reflection of the expert knowledge base, scope of practice and interdisciplinary nature of the emerging model for health care delivery.…”
Section: Discussionmentioning
confidence: 76%
“…There is no regulation in Denmark for advanced nursing practice . Reforms in Denmark changed nursing education from an apprenticeship model to one requiring a university‐based system; in 1990 Denmark established the bachelor's degree as entry‐level for nursing, called Sygeplejerske (certified nurse).…”
Section: Discussionmentioning
confidence: 99%